Uji Produktivitas Calon Bibit G3 FP005 Jamur Merang (Volvariella volvaceae) Faperta Unsika Menggunakan Jerami dengan Metode Pemanenan Berbeda di Desa Majalaya Kabupaten Karawang - Abelawana, Fadhlan; Syah, Bastaman; Lestari, Ani (JURNAL AGROPLASMA, 2023)
Mushroom is one type of mushroom that is quite widely known by the people of Indonesia. This straw mushroom is included in the agricultural commodity of horticultural crops where the economic value is quite high. The current problems of mushroom cultivation are straw mushroom seeds, straw mushroom growing media, and rice straw harvesting techniques. The purpose of this study was to compare the characteristics of the mushroom (Volvariella volvaceae) on straw media with different harvesting methods (gebot, combineÂ¸ and trasher). The research was conducted in a farmer's straw mushroom house located in Pasir Buah Hamlet, Pasirmulya Village, Majalaya District, Karawang Regency. In November-December 2022. The research method used was a single factor Randomized Block Design (RBD) with 3 replications. There are 12 treatments, namely A (Gebot 100%), B (Combine 100%), C (Trasher 100%), D (Gebot 50% + Combine 50%), E (Gebot 50% + Trasher 50%), F (Combine 50% + Trasher 50%), G (Gebot 75% + Combine 25%), H (Gebot 75% + Trasher 25%), I (Combine 75% + Trasher 25%), J (Gebot 25% + Trasher 75%) K (Combine 75% + Trasher 25%), L (Trasher 75% + Combine 25%). The effect of treatment was analyzed by analysis of variance and if the F test at 5% level was significant, then to find out which treatment was the best, it was continued with the DMRT follow-up test (Duncan Multiple Range Test) at the level of 5%. There was a significant effect on the number of fruit bodies, body weight per fruit tray, and fruit body weight from the productivity test of G3 FP005 mushroom seeds with media combine 75% + trasher 25% can be used as a reference material for the growth of straw mushroom, because it has better results than other treatments for the growth and development of straw mushroom.Â Keywords:G3 Faperta Isolate, Straw Mushroom, Straw Harvesting MethodÂ